Pengaruh Kompetensi Digital dan Knowledge Sharing Terhadap Kinerja Tenaga Kependidikan Dengan Motivasi Sebagai Variabel Intervening - Feny Yulita; Chalimah; Wahyuningsih (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
The difference in research results on the influence of digital competence, knowledge sharing, motivation on performance underlay this research. The purpose of this study was to test and analyze the influence of digital competence and knowledge sharing on the performance of educational staff at Pekalongan University with motivation as an intervening variable. Data analysis in this study used the Partial Lest Square (PLS) approach. The results of the study explained that: First, digital competence had a positive and significant effect on motivation. Second, digital competence had a positive and insignificant effect on performance. Third, knowledge sharing had a positive and significant effect on motivation. Fourth, knowledge sharing had a positive and significant effect on performance. Fifth, motivation had a negative and insignificant effect on performance. Sixth, digital competence had a direct effect on performance, meaning that motivation did not play a role in mediating the relationship between digital competence and performance. Seventh, knowledge sharing had a direct effect on performance, meaning that motivation did not play a role in mediating the relationship between knowledge sharing and performance. Keywords : digital competence, knowledge sharing, performance, motivation